2021
DOI: 10.1088/1755-1315/808/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Multiple regression model for gas consumption in Germany

Abstract: In this paper a mathematical regression model was constructed based on statistical data on natural gas consumption in the Federal Republic of Germany (FRG). Two factors that can influence gas consumption were studied: the country’s population and the average annual temperature. On the basis of the calculations, the importance of these indicators for gas consumption is shown, with the conclusion that the climatic factor is normally distributed. The reliability of the model is high (99.98%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Makala [22] made an attempt to analyze the relationship between industrial growth and natural gas consumption, his research focusing on finding a relationship between natural gas consumption and economic growth in Tanzania. The other notable publication is the analysis of the natural gas market in Germany [23], in which the authors analyze the factors in the construction of a statistical model of natural gas consumption. It is indicated that the main factors are population and outdoor temperature.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Makala [22] made an attempt to analyze the relationship between industrial growth and natural gas consumption, his research focusing on finding a relationship between natural gas consumption and economic growth in Tanzania. The other notable publication is the analysis of the natural gas market in Germany [23], in which the authors analyze the factors in the construction of a statistical model of natural gas consumption. It is indicated that the main factors are population and outdoor temperature.…”
Section: Review Of the Literaturementioning
confidence: 99%